The ‘Spirit’ of Schooling: The relevance of the sense of a calling on the school experiences of secondary-school Roma/Ciganos students - Pedro Caetano; Mendes, M. M. (Intersections. East European Journal of Society and Politics, 2024)
In The Protestant Ethic and the Spirit of Capitalism (PE), Max Weber examines the ecological domination of instrumental rationality to the detriment of value-oriented action. The concept of the calling (Beruf in German) becomes a key one for interpreting the process of value rationalization. One can find Weberian value-rationality among the Portuguese Roma/Ciganos, who seek alternative livelihood strategies via schooling, although they are still characterized by a high rate of early school dropouts, with a very low number of students attending secondary education. The EDUCIG (School performance among Ciganos/Roma: action research and co-design) project was launched in 2019 to grasp the multiple factors involved in this social problem. The project interview-based analysis entailed the participation of 31 Roma/Ciganos students from the metropolitan areas of Lisbon and Porto. Results suggest that despite the social, cultural and economic constraints affecting their school pathways, the academic success of young Roma/Ciganos is facilitated by the influence of religion, specifically the Pentecostal Evangelical Church and its respective values. Moreover, we can recognize the emergence of a new ‘spirit’ in these young Roma/Ciganos, a ‘spirit’ that does not aim at instant gratification but represents an investment in the future and, simultaneously, a desire for integration.